2020
DOI: 10.1093/jcmc/zmz028
|View full text |Cite
|
Sign up to set email alerts
|

New Rules of Engagement: How Adaptation To Online Media Changes Older Adults' Social Connectedness

Abstract: Older adults often struggle to adjust to the rapid changes in the digitizing media landscape. In this article, we study, first, how 10 older adults adapt new online media into their daily lives and, by doing so, adjust to the changing “rules of engagement” that guide online-media use in their social surroundings. Second, we analyze how this adaptation process generates change in older adults' social connectedness. Results suggest that older adults' non-use of popular online media results in social exclusion. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The majority (90%) of the mature applicants of the University of Ghana were engaged via the Sakai learning platform followed by zoom (76.1%), emails (53.1%), and then WhatsApp (47.6%). This indicates that, unlike the observations by Hage et al (2020) , adult learners are building their confidence in online learning. What is critical is to orient them to enhance their utilization of learning management systems as noted by Dampson et al (2020) .…”
Section: Discussion Of Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The majority (90%) of the mature applicants of the University of Ghana were engaged via the Sakai learning platform followed by zoom (76.1%), emails (53.1%), and then WhatsApp (47.6%). This indicates that, unlike the observations by Hage et al (2020) , adult learners are building their confidence in online learning. What is critical is to orient them to enhance their utilization of learning management systems as noted by Dampson et al (2020) .…”
Section: Discussion Of Resultsmentioning
confidence: 56%
“…Information Technology jargon such as online, Google, Internet, and login do not often mean anything to adult learners. Adults also have to cope with emotional reactions like fear, enjoyment, curiosity, frustration, and stress especially when they feel old, not well educated, not experienced in technology, and unable to operate basic gadgets ( Hage et al, 2020 ). The majority (90%) of the mature applicants of the University of Ghana were engaged via the Sakai learning platform followed by zoom (76.1%), emails (53.1%), and then WhatsApp (47.6%).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Such a threat to external validity has also been an issue in previous, related lab experiments (e.g., Hunter et al, 2018;Knausenberger & Echterhoff, 2018;Sestir, 2020). However, as social bonds are crucial for the health of older people who may use social media and smartphones differently to cope with threatened belongingness (Chen & Schulz, 2016;Hage et al, 2020), this needs to be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults often face age-related barriers that can cause them to be hesitant in adopting digital devices such as a lack of digital skills, not knowing digital jargon, limited confidence, and the hindrance of small screens and hard to press buttons (Hage et al, 2020; Neves et al, 2019; Quan-Haase et al, 2018). Despite the barriers, studies have found older adults are not a homogenous group.…”
Section: Literature Reviewmentioning
confidence: 99%